(untitled) (The Science Post, 2025)
This study examines the transformative potential of Artificial Intelligence (AI) in shaping learning outcomes within Bangladesh’ s evolving educational landscape. Leveraging a mixed-methods approach that integrates large-scale surveys, in-depth interviews, and secondary data analysis, the research explores how AI-driven tools—ranging from intelligent tutoring systems to adaptive learning platforms — impact student performance, engagement, and personalized instruction across K–12 and higher education sectors. Findings reveal that AI can significantly enhance academic achievement, foster individualized learning experiences, and improve teaching efficiency when supported by robust infrastructure, teacher readiness, and localized digital content in Bangla. However, challenges such as limited technological capacity in rural regions, unequal access to digital resources, and concerns around data privacy, algorithmic bias, and ethical governance constrain large-scale adoption. The study highlights strategic pathways for integrating AI responsibly and sustainably, offering policy recommendations for government agencies, educational institutions, and EdTech developers. These include capacity-building initiatives, inclusive digital infrastructure development, and regulatory frameworks that ensure equity, cultural alignment, and data security. Ultimately, the research underscores AI ’ s potential to drive inclusive educational innovation in Bangladesh while addressing systemic barriers to its effective implementation.